PERANCANGAN SISTEM INFORMASI PENJUALAN PADA TOKO JAYA JAMBI - Shobur, Ahmad Ferdian; Helmina, Helmina; Santoso, Heri (LPPM Universitas Muhammadiyah Jambi, 2022)
A shop building Jaya Jambi is one of the company that moves in the fields of a sale and purchase goods , that experienced competition been tough enough with the company the like. In enhancing the quality of service to customers the company requires a good system. Thus should be designed a information systems that aims to devise a system in process data selling in a shop building Jaya Jambi computer that is based , in order to process an employee in the selling data and the purchase of or effectiveness in for finding data and prepare reports. In this study researchers used a Tools of UML (Unified Modeling Language), method Waterfall and using language programming VB.NET. This research produce information system sales in stores jaya jambi that can manage the data of goods , the purchase , sales of , retur and report the purchase , sales reports , reports the percentage of sales and the report retur it was.